MEMINIMALISIR PEMBIAYAAN BERMASALAH DALAM PEMBERIAN PEMBIAYAAN MIKRO DENGAN PRINSIP 5C - Damayanti, Laila; Tobibatussaadah, Tobibatussaadah; Nuriasari, Selvia (Mu'amalatuna: Jurnal Ekonomi Syariah, 2020)
The micro financing offered by BRIS KCP Metro is financing that is used for productive purposes in micro businesses. Micro Financing certainly carries the risk of problem financing which can increase the NPF BRIS value which affects the financial performance of BRIS. It is known that the NPF BRIS has increased quite significantly from 2017 to 2018, namely from 1.9% to 9.4% which explains the increase in problem financing in BRIS. To minimize this problematic financing, BRIS KCP Metro has strengthened the implementation of the 5c principle before distributing microfinance to the community. This research is a descriptive qualitative study that describes the application of the 5c principle in minimizing problematic micro financing at BRIS KCP Metro. The primary data sources are Unithead employees, BRI Syariah KCP Metro Micro Account Officer employees and problematic Micro Financing customers. The result of the research is the 5c principle in minimizing problematic micro financing in BRIS KCP Metro still needs improvement and evaluating several aspects of 5C, namely the aspect of character assessment and the aspect of capacity assessment. The weak application of character assessment for prospective customers is due to the inexperience of AOM employees which has resulted in increased financing problems due to dishonest customers in using these funds. Then AOM's weakness in assessing the business capacity of prospective customers is seen from AOM's mistakes in calculating or estimating the size of the accounts contained in the capacity component, because in micro businesses, well-structured financial reports are very rare. As a result of these two things, the NPF value increases every year. Therefore it is necessary to provide training for AOM employees to improve soft skills in analyzing 5Cs, and the need for periodic monitoring after disbursement so that the funds channeled are used in accordance with the proposals submitted by prospective customers.